Odpowiedzi

2010-01-06T17:20:26+01:00
A) 4x-(x+6)+4 dla x=⅓
4x-(x+6)+4=3x-2=1-2=-1
B) (x²+1)-(x²-2)+10 dla x =2,2
(x²+1)-(x²-2)+10=x²+1-x²+2+10=13
C)(a+4b)-(5+2a)-(3b-5) dla a=-0,1 i b=0,2
(a+4b)-(5+2a)-(3b-5)=a+4b-5-2a-3b+5=-a+b=0,1+0,2=0,3
5 3 5
2010-01-06T17:32:00+01:00
A) 4x-(x+6)+4 dla x=jedna trzecia
4x - x - 6 + 4 = 3x - 2
3 razy 1/3 - 2 = 1 - 2 = -1
B) (x do kwadratu +1)-(x do kwadratu - 2) + 10 dla x =2,2
(x² + 1) - (x² - 2) + 10 = x² + 1 - x² + 2 + 10 = 13
C)(a+4b)-(5+2a)-(3b-5) dla a=-0,1 i b=0,2
a + 4b - 5 - 2a - 3b + 5 = -a + 2b = 0,1 + 0,4 = 0,5
5 3 5